2018
DOI: 10.1080/13543784.2018.1471135
|View full text |Cite
|
Sign up to set email alerts
|

Investigational drugs for the treatment of endometriosis, an update on recent developments

Abstract: Endometriosis is a hormone-dependent benign chronic disease that requires a chronic medical therapy. Although currently available drugs are efficacious in treating endometriosis-related pain, some women experience partial or no improvement. Moreover, the recurrence of symptoms is expected after discontinuation of the therapies. Currently, new drugs are under intense clinical investigation for the treatment of endometriosis. Areas covered: This review aims to offer the reader a complete and updated overview on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 166 publications
(138 reference statements)
0
18
1
2
Order By: Relevance
“…This statement is in agreement with the pathogenetic theory of retrograde menstruation. Indeed, the pelvic contamination, as well as the implant risk, is higher due to more regular short periods and heavy bleeding lasting for more than seven days [3,7,45]. In our study, we did not register any connection between regularity of menstrual cycle and endometriosis.…”
Section: Plos Onecontrasting
confidence: 53%
See 3 more Smart Citations
“…This statement is in agreement with the pathogenetic theory of retrograde menstruation. Indeed, the pelvic contamination, as well as the implant risk, is higher due to more regular short periods and heavy bleeding lasting for more than seven days [3,7,45]. In our study, we did not register any connection between regularity of menstrual cycle and endometriosis.…”
Section: Plos Onecontrasting
confidence: 53%
“…Several previous studies [2,7] have shown that the characteristics of the menstrual cycle are strictly related to endometriosis: regular, short cycles and heavy bleeding lasting for more than seven days are associated with the development of the disease. This statement is in agreement with the pathogenetic theory of retrograde menstruation.…”
Section: Plos Onementioning
confidence: 98%
See 2 more Smart Citations
“…Thus, there still is the need to develop new medications for this purpose. 8 Thalidomide has a potent antiangiogenic effect based on the negative regulation of vascular endothelial growth factor (VEGF). In addition, thalidomide functions as an immunomod-ulator and as an immunosuppressor and anti-inflammatory agent since it acts on the excessive synthesis of Tumor necrosis factor-alpha (TNF-α) and of other cytokines such as interleukin 6, which participate in the genesis of inflammatory pain.…”
Section: Introductionmentioning
confidence: 99%